Green entrepreneurial orientation, boundary-spanning search and enterprise sustainable performance: The moderating role of environmental dynamism - 叶, Ye 芳.; Yang, Yi; Shao, Yi X.; Xia, Hai y.; Gu, Xie G. (Frontiers in Psychology, 2022)
As an important strategic decision for enterprise sustainability, the green entrepreneurial orientation can facilitate boundary-spanning search for external knowledge and resources to achieve triadic sustainable economic, environmental, and social performance. Based on organizational search theory and dynamic capability theory, this study introduces environmental dynamism into the model of the relationship between green entrepreneurial orientation, boundary-spanning search and enterprise triadic sustainable performance. By analyzing the questionnaire data from 202 managers of manufacturing SMEs, the study explores the internal and external influences of green entrepreneurial orientation on the enterprise sustainable performance. The results show that: green entrepreneurial orientation has a positive impact on enterprise economic, environmental and social performance; boundary-spanning search plays a fully mediating role between green entrepreneurial orientation and enterprise economic, environmental and social performance; environmental dynamism, as a key external environmental factor, positively regulates the relationship between boundary-spanning search and enterprise economic performance and environmental performance, and negatively regulates the relationship between boundary-spanning search and social performance. This study clearly demonstrates how green entrepreneurial orientation in the environmental era can drive triadic sustainable performance improvement of enterprises. In addition, this study argues that boundary-spanning search is an important tool that enables manufacturing SMEs to achieve a triad of coordinated sustainable development of economic, environmental and social benefits in a dynamic environment.